Poly (N-tert-amylacrylamide -co- Acrylamide/ Sodium acrylate) Fe3O4 Nanocomposite Hydrogels as polymer catalyst for the reduction of Methylene Blue Dye - Pazhnaisamy, P.; Hidayah, Euis Nurul; Sulania, Indra (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2022)
Fe3O4 Nanocomposite Hydrogels were prepared by free radical polymerization using N-tert-amyl acrylamide , Acrylamide and Sodium acrylate monomers at 60OC. Fe3O4 NPs was intercalated via in situ method. The synthesized nanocomposite Hydrogels conformed by FT-IR spectroscopy. Surface morphology of the nanocomposite hydrogels indicated the ferrate nanoparticles are intercalated uniformly throughout the polymer matrix. The XRD pattern of the hydrogel showed the presence of nanoparticles in the matrix with certain crystallinity nature. UV-visible absorption studies reveal the catalytic activity of Methylene Blue dye molecules in the aqueous medium by the Nanocomposite hydrogels.